Riesgos de las estrategias genéricas y competitividad en las microempresas de videojuegos - provincia de Huancayo (2020) - Suarez Agreda, Humberto Jesús (2023)
The study carried out defines the magnitude of the link within the study variables; where using the technique of quantitative analysis, agglomerating information to verify this assumption, using statistics to understand the behavior of the variants, revealing as a consequence the decrease in competitiveness if there is no appropriate inspection of the variants. Finally, the Cramer factor gives us 0.890 this requires a strong link of 89% between rivalry and threats, it is inferred that the link in the model indicates a real grouping between the variables analyzed.